HOW IMPORTANT EDUCATION IS? AN EXPLORATIVE ANALYSIS OF THE DROPOUT PHENOMENON IN EASTERN EUROPE - Piera CASCIOLI; Emiliano COLANTONIO; Daniel BADULESCU (Annals of the University of Oradea: Economic Science)
Early school leaving is a structural problem related to the socioeconomic environment involving aspects of local culture and customs that characterize a country. If not controlled, with the intent of hindering it, this phenomenon can generate unemployment, social exclusion, poverty, health problems and a slowdown in the country’s economic growth. Since education policies are one of the most important concerns of national governments and international organizations, the UN 2030 Agenda, containing the common ambitions of the signatory countries, proposes 17 sustainable development goals and specifically, among these, inclusive and equitable quality education. In some Eastern European countries, the percentage of young people who decide not to continue their studies is really too high, exceeding 10%. Therefore, the aim of the paper is to study the dropout phenomenon in this context. We employ a panel vector autoregressive model in first differences to test complex dynamic relationships between share of the population aged 18 to 24 not involved in any education or training (as a proxy for the dropout phenomenon), GDP per capita (as a proxy for a country’s wealth and industrial modernity), gross domestic expenditure on R&D in higher education (as a proxy for a country’s effort to improve its education system), and share of people reporting crime, violence or vandalism (as a proxy for a country’s social condition). The study concerns 10 Eastern European countries for the period 2000-2021. The results show that the government expenditure in education is negatively related to the dropout rate. Moreover, the increase in the relative number of early school leavers seems to stimulate a worsening in social conditions, with an increase in cases of crime, violence and vandalism. Finally, both an increase in dropouts and a deterioration in social conditions generate negative effects on the well-being of the community and economic growth. Improving the quality of the education system is therefore crucial (this is also confirmed by the variance decomposition analysis), even if it may not be enough: from the impulse response functions analysis, indeed, a shock exerted on the government expenditure on R&D in higher education produces positive effects on the (declining) dropout rate, but only for a short period. Policymakers should therefore make constant efforts to reduce the early school leaving.